Invasive pneumococcal disease in patients with an underlying pulmonary disorder. (7th March 2013) - Inghammar, M.; Engström, G.; Kahlmeter, G.; Ljungberg, B.; Löfdahl, C.‐G.; Egesten, A.; Paul, M.
Abstract Chronic pulmonary disease is a recognized risk factor for invasive pneumococcal disease (IPD). However, previous studies have often not been large enough to allow detailed analyses of less prevalent pulmonary diseases, and findings regarding case fatality have been inconsistent. We examined the associations between an underlying pulmonary disease and IPD, and the impact of these diseases on the case fatality rate. Patients with IPD ≥18 years of age, between 1990 and 2008, were identified in microbiological databases. The associations between IPD and the pulmonary diseases were assessed using conditional logistic regression, comparing IPD cases to ten control subjects per case, randomly selected from the general population (matched for gender, year of birth and county of residence). Adjustments were made for other co‐morbidities, level of education and socio‐economic status, 4085 cases of IPD and 40 353 controls were identified. A more than four‐fold increased risk of IPD was seen in chronic obstructive pulmonary disease, a doubled risk in asthma and a five‐fold increased risk in subjects with pulmonary fibrosis. In univariate analysis, sarcoidosis and bronchiectasis were associated with a two‐fold to seven‐fold increase in the risk of IPD, but there was no statistical support for the associations when adjustments for confounders were made. No increased risk was seen in subjects with a history of pneumoconiosis or allergic alveolitis. The mortality following IPD was not increased in patients with chronic obstructive pulmonary disease, asthma, pulmonary fibrosis or bronchiectasis. Several chronic pulmonary diseases increase the risk of IPD but mortality following IPD seems not to be affected.